(untitled) (International Journal of Engineering and Computer Science, 2018)
Threat in any system can be identified only when we have full knowledge of the system. And threats can also be prevented if proper tools or mechanisms are present or developed. So, this paper review not only identifies the problem in Wireless LAN but also reviews previously proposed solutions to the threats that exploit communication through WLAN. And presents new prevention mechanism to the existing problem with securing its main server. The paper reviews the experiments conducted to study the impact of various attacks on the system and also post solution results evaluation. A hybrid approach is used for deep packet inspection over network traffic to resolve unauthorized access in WLAN, provide satisfactory results in performance.